Association of Hypertension with Body Mass Index (Bangladesh Journal of Neuroscience, 2018)
Background: Body mass index (BMI) is positively associated with blood pressure (BP). Weight loss significantly reduces blood pressure (BP).The principal aim was to find out the association of Body Mass Index (BMI) with hypertension.Methods: This crosssectional study was conducted at outpatient department of Bangabandhu Sheikh Mujib Medical University (BSMMU). A total of 1128 hypertensive patients were included in this study by purposive sampling method. Staging of hypertension was done according to The JNC 7 Hypertension Guidelines. BMI was calculated by measuring weight in kilograms divided by height in meters squared.Results: This study demonstrated that majority (58.1%) were within 40 to 60 years. 63.7% patients were male and 36.3% were female. Maximum observed systolic blood pressure was 170 mm of Hg and minimum 110 mm of Hg. Maximum diastolic blood pressure was 120 mm of Hg and minimum 60 mm of Hg. Out of 1128 hypertensive patients’ 21% patients had normal BMI, 66.7% overweight, 8.8% obese and 3.5% patients were under weight. So hypertension was found more in overweight study subjects which was found statistically significant.Conclusion: The prevalence of hypertension is more in increased BMI.Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 92-95